Ein geographisch bestimmtes System der Wirthschaftslehre: Raumkonzepte und Standorttheorien des ökonomischen Historismus - Scheuplein, Christoph (ERDKUNDE, 2007)
Economic historicism in the discipline of economics has separated itself from classical political economy by focusing on specific conditions of national economic spaces. This integration of the spatial dimension was influenced by the newly founded field of human geography in the first half of the 19th Century. The new approach led to an intensive inquiry into the economy of space. National territories were conceptualized as production systems and spatial patterns of industry were described. The Historical School of Economics advocated a problematic environmental determinism as a methodology. However, the historicists were able to present changes in industrial spaces as a complex socio-economic process.